An epidemic methicillin-resistant strain of Staphylococcus aureus in Spain. - Aparicio, P. (Cambridge University Press, 1992)
During 1990, a strain of methicillin-resistant Staphylococcus aureus became epidemic in Spain and spread in a manner analogous to that of EMRSA-1 in England. Isolates of this strain produced little protein A and were resistant to a number of antibiotics including ciprofloxacin. Beta-lactamase production was encoded by a c. 39 kb plasmid, which also conferred resistance to mercury, cadmium, ethidium bromide and propamidine isethionate. Investigation showed that two variants, separable by supplementary and Fisk phage typing, were circulating. The B variant appeared to spread more readily than the A variant. The opportunity was taken to compare the discriminatory power of traditional typing methods with molecular techniques. The discriminatory power of the molecular techniques used only reached the same level as the traditional methods when double enzyme digestion of total cellular DNA by EcoR I and Cla I was performed.